Marks' essentials of medical biochemistry a clinical approach - Lieberman, Michael 1950-; Peet, Alisa (Wolters Kluwer, 2015)
Based on the Marks' Basic Medical Biochemistry, this book is streamlined to focus only on the essential biochemical concepts, while maintaining intuitively organized chapters centered on hypothetical patient vignettes and icons for navigation.